The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1186/1744-8603-9-57
|View full text |Cite
|
Sign up to set email alerts
|

From scaling up to sustainability in HIV: potential lessons for moving forward

Abstract: BackgroundIn 30 years of experience in responding to the HIV epidemic, critical decisions and program characteristics for successful scale-up have been studied. Now leaders face a new challenge: sustaining large-scale HIV prevention programs. Implementers, funders, and the communities served need to assess what strategies and practices of scaling up are also relevant for sustaining delivery at scale.MethodsWe reviewed white and gray literature to identify domains central to scaling-up programs and reviewed HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 11 publications
1
31
1
1
Order By: Relevance
“…The literature on health program sustainability has referred to this distinction as one between the core components and the customizable components of interventions [1517, 23]. Hirschhorn et al [13] have called for an appropriate balance between adaptation and flexibility in the scale-up of HIV interventions [46]. In contrast with a previous study [45], we found that most modifications to ART were made at the organization level as opposed to individual clinicians.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The literature on health program sustainability has referred to this distinction as one between the core components and the customizable components of interventions [1517, 23]. Hirschhorn et al [13] have called for an appropriate balance between adaptation and flexibility in the scale-up of HIV interventions [46]. In contrast with a previous study [45], we found that most modifications to ART were made at the organization level as opposed to individual clinicians.…”
Section: Discussioncontrasting
confidence: 68%
“…Devising service delivery models that are suited to resource-limited contexts is acknowledged as an important strategy for fostering the sustainability of ART scale-up programs in SSA [10, 11]. Service delivery design alternatives to the traditional model of physician-centered, clinic-based care are becoming critical in SSA [4, 12, 13]. Sustaining and expanding ART coverage in resource-limited settings requires modifications and adaptations of ART delivery models to meet the continually rising demand [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…They related to cost-effectiveness, equity, harms, ethics, bottom-up/top-down scaling-up, and the context in which the EBI was scaled up (see Figure 2). To discuss them, we identified 45 scaling-up studies that raised these difficulties, of which 13 were on costeffectiveness estimates or cost-analysis models [22][23][24][25][26][27][28][29][30][31][32][33][34], 14 on equity [35][36][37][38][39][40][41][42][43][44][45][46][47][48], four on harms [16,[49][50][51][52], three on ethics [53][54][55], six on top-down implementation [42,[56][57][58][59][60], and eight on contextual problems [40,43,[61][62][63][64]…”
Section: Introductionmentioning
confidence: 99%
“…The health inequities pitfall: some people will necessarily be left out Many studies highlight equity as a motive for scalingup effective healthcare interventions: an EBI that is delivered only to a small population constitutes a health inequity, as others are deprived of its proven health benefits [36,[38][39][40]42,43,[46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…Research focused on the transmission of communicable diseases, and the influence that globalisation has on the spread of these [34, 35]. Most papers were in relation to HIV and AIDS, and included HIV programme sustainability, access to interventions and adherence to treatments [17, 36, 37]. Sustained use and access to antiretroviral therapy was another frequently occurring topic under this construct.…”
Section: Resultsmentioning
confidence: 99%